Enhanced Flipping Technique to Reduce Variability in Image Steganography - Kamil S.; Abdullah S.N.H.S.; Hasan M.K.; Bohani F.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Benchmarking; Discrete cosine transforms; Genetic algorithms; Image coding; Image enhancement; Mean square error; Signal to noise ratio; Bayes method; Cover-image; Data hidden; Embedding capacity; Flipping methods; Least significant bits; Medium; Optimisations; Variability; Visual qualities; Steganography